Konstruktivisme Model Pembelajaran Kognitif Moral Melalui Aplikasi “Dimo” Untuk Meningkatkan Kemampuan Moral Decision Siswa Sekolah Dasar - Faiz, Aiman; Fadly, Aris (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
To offset the concerns that arise due to changes in human behavior caused by rapid and unstoppable technological advances, the field of education needs to provide various reinforcements, one of which is through the learning process. Research to see the improvement of elementary school students' moral decisions through the cognitive moral development model assisted by the